Design of fuzzy PI controller for CSI fed induction motor drive / Piush Kumar, Vineeta Agarwal and Asheesh K. Singh - Kumar, Piush; Agarwal, Vineeta; K. Singh, Asheesh (UiTM Press, 2011)
In this paper the closed loop control of CSI fed induction motor is investigated using fuzzy logic controller. A slip control scheme has been used for the induction motor. The evaluation of the fuzzy logic controller behavior is made through computer simulation with MATLAB coding. The starting transient of the motor is investigated for different operating speeds with different load torque. It has been found that for fuzzy controller, once the parameters are selected for a specified load and speed it will work for all other load and speed whereas for conventional PI controller, the parameters have to be changed for each load and speed setting. The fuzzy controller reduces the over shoot value of speed by approximately 2 to 5 % while for dc link current it reduces around 4% as compared to conventional PI controller. This reduces the rating of the devices used in the drive system. It has also been found that the system shows some what slow response with less oscillation so that fuzzy controller can be used where smooth operation is required.